ASSESSMENT OF THE DEGREE OF IMPLEMENTATION OF THE RESULTS OF SCIENTIFIC RESEARCH AND INVENTIONS IN THE AGRICULTURAL SECTOR OF THE ECONOMY - Elena DERUNOVA; Marianna VASILCHENKO; Anton VORONOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In ensuring the country's food security, the dominant role belongs to scientific activity and the development of advanced production technologies. Moreover, the process of implementation of innovations and further stimulation of demand for the results obtained are of greatest relevance. The purpose of the study is to develop theoretical and methodological approaches to assessing the implementation of scientific developments and new technical solutions in agriculture in the context of innovative transformation of the economy. The article reveals significant interregional and intercountry differentiation of patent activity, and notes the gap between the total number of patents and the inventions being introduced into Russian agriclture. Based on a scientometric analysis of patents with text mining, trends and patterns in the formation of promising patent developments in agriculture have been identified and a bibliometric map has been generated in the direction of the relationship between areas of patent activity in Russian agriculture. The predominant clusters have been identified - agricultural engineering; soil treatment, harvest, pest control, production of herbicides and their components. The results obtained determine the need to develop effective mechanisms for supporting patent activity in agriculture and stimulating the introduction of scientific developments and new technical solutions into the production process in order to determine the most promising areas of research in agricultural science. The practical implementation of the research results is associated with the justification of the necessary incentive measures and government support for scientific developments in the context of fundamental technological changes and innovative structural shifts.